THE IRRATIONAL BELIEFS OF BALINESE FEMALE OFFICE WORKERS - PURNAWATI, SUSY; PRIMAYANTI IDA, INTEN DWI; IN, ADIPUTRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This preliminary study aimed to explore the score of irrational beliefs (IBs) among Balinese female office workers in Gianyar. This is a new and very interesting issue in occupational mental health practice in Bali and Indonesia. The finding of this study will be able to use as information for an authority to create some program improvement for human resources at work setting. Methods: This study used a cross-sectional study design involved 30 participants. In this study, we measured the IBs score by self-reported questionnaire of the smith IB inventory which contained 24 items statement. Results: The means age of participants was 40.4 years old and means the length of stay was 15.2. years. In this preliminary study, we found the means score of IBs score was 52.37±10.460 (high score category). Conclusion: The score of IBs of Balinese female office workers in Gianyar was high score category. This result has a clinical impact as well as the outcome of this study can be used to be a recommendation to the government or organization to create an awareness program to decrease worker’s IBs score in purposing better their mental health, work productivity, and well-being.